2018
DOI: 10.1039/c7ra11475c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of bio-based nitrogen- and oxygen-doped porous carbon derived from cotton for supercapacitors

Abstract: Biomass-derived O- and N-doped porous carbon has become one of the most competitive supercapacitor electrode material because of its renewability and sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This leads to an increase in the I D /I G ratio due to oxidation of the carbon which results in addition of oxygen functional groups in the Sb 2 O 4 /C composite. As a consequence of this, there is an increase in defect/disorder in the composite . This is beneficial in its application as anode material for Na ion battery since it has been reported that Na ions exhibit greater binding affinity towards these sites leading to better slope capacity in galvanostatic charge/discharge profiles .…”
Section: Resultsmentioning
confidence: 99%
“…This leads to an increase in the I D /I G ratio due to oxidation of the carbon which results in addition of oxygen functional groups in the Sb 2 O 4 /C composite. As a consequence of this, there is an increase in defect/disorder in the composite . This is beneficial in its application as anode material for Na ion battery since it has been reported that Na ions exhibit greater binding affinity towards these sites leading to better slope capacity in galvanostatic charge/discharge profiles .…”
Section: Resultsmentioning
confidence: 99%
“…N-Q can also contribute to electron transport 37 , 62 . In the fitting of O1s spectra, all samples that revealed two peaks at 531.3 eV and 533.2 eV were assigned to the C=O carbonyl- or quinone-type groups and C–OH phenol or C–O–C ether groups, respectively 18 , 42 , 63 .
Figure 3 ( a ) XPS survey spectrum taken from the surface of N-CPC-800 sample.
…”
Section: Resultsmentioning
confidence: 99%
“…[ 55 ] It is important to note that OH or COC is beneficial to enhance the wettability of the electroactive material in the aqueous system. [ 56 ] Also, only the quinone‐type oxygen is electrochemically active in acidic medium (Equation (6) and (7)), [ 57 ] which will eventually contribute in improving the pseudocapacitance of the TLPC‐900 material. Similarly, the N 1s spectrum (Figure 3e) is deconvoluted into three individual peaks as graphitic‐N (403 eV), [ 58 ] prollic‐N (399.65 eV), and pyridinic‐N (397.43 eV).…”
Section: Resultsmentioning
confidence: 99%